2015
DOI: 10.1007/s00384-015-2358-8
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer patients after neoadjuvant radiotherapy (30Gy/10f) with negative lymph node may not benefit from postoperative adjuvant chemotherapy: a retrospective study

Abstract: Based on a Chinese protocol, patients with ypN- stage may not benefit from adjuvant chemotherapy, regardless of the ypT stage, while the ypN+ patients may benefit from adjuvant chemotherapy. More randomized clinical trials are needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In locally advanced rectal cancer, neoadjuvant chemoradiotherapy with a total mesorectal excision is the standard of treatment, as it can downstage the disease [6,[10][11][12][14][15][16]. Furthermore, reduction in the lymph node staging is seen in 30-60% of lymph node-positive patients [16,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In locally advanced rectal cancer, neoadjuvant chemoradiotherapy with a total mesorectal excision is the standard of treatment, as it can downstage the disease [6,[10][11][12][14][15][16]. Furthermore, reduction in the lymph node staging is seen in 30-60% of lymph node-positive patients [16,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The use of adjuvant chemotherapy especially in the context of previous neoadjuvant treatment, is controversial . Fluoropyrimidine‐based adjuvant chemotherapy has been widely used, and the addition of oxaliplatin was based on data from patients with colon cancer . For many years colon and rectal cancers were considered as a single entity and much of the evidence looking at the use of adjuvant therapy in rectal cancer is taken from studies looking at colon and rectal cancer together.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with LARC who underwent NCRT followed by curative surgery, ypN stage is regarded as the strongest independent prognostic factor influencing oncological outcomes [ 29 ]. Several studies analysed the prognostic value of adjuvant chemotherapy for patients with ypN– and ypN+ tumors and found that adjuvant chemotherapy may be unnecessary for those with ypN– disease and that only patients with ypN+ tumors were candidates for adjuvant chemotherapy [ 14 , 18 ]. Pathological T stage is also a powerful prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%